Electroclinical characteristics of photosensitive epilepsy: A retrospective study of 31 Chinese children and literature review - Zhang, Bo; Chen, Tianyu; Hao, Xiaosheng; Xin, Meiying; Liang, Jianmin (Frontiers in Pediatrics, 2023)
Objective: To better understand clinical features of photosensitive epilepsy (PSE) in Chinese children. Methods: Thirty-one cases of PSE children were screened out in 398 children with epilepsy who consecutively diagnosed by video-electroencephalogram (VEEG) monitoring and intermittent photic stimulation (IPS) test. The EEG and clinical features of them were retrospectively analyzed, and their treatment outcomes were followed up. Results: PSE accounted for 7.79% (31/398) of Chinese children with epilepsy during the observation period in our single epilepsy center. The male to female ratio of PSE was 1:3.43 and the average seizure onset age was 7.8 m4±3.28 years. The most sensitive frequency range of the IPS test for the induction of EEG epileptic discharges or electro-clinical seizures (ECSs) was within 10～20Hz. Electro-clinical seizures were induced in 41.94% (13/31) PSE patients in the IPS test, while 58.06% (18/31) PSE patients were induced only EEG discharge without clinical seizure. Among all the PSE patients, 83.87% were induced IPS positive reaction in the eye-closure state, which was significantly higher than that of eye-opened state (41.94%) or eye-closed state (35.48%). The common and effective drugs used for single or combined therapy in PSE children were valproic acid (VPA) and levetiracetam (LEV). Conclusions: This study provides some useful information of electro-clinical characteristics in a cohort of 31 PSE Chinese children. It may be benefit for pediatric neurologists to pay more attention to PSE and deal with it correctly.